Analysis of the Influence of Community Perceptions in Ambon on Sharia Fintech - Nurlette, Erlin D. P.; Nacikit, Muhammad R; Shalihah, Maratun; Maruapey, Muammar W; Yaman, Afdhal; Malawat, Fadli F; Hamizar, Arizal (Rangkiang: Journal of Islamic Economics and Business, 2024)
This research aims to determine the perception of the people of Ambon city regarding the existence of sharia fintech in Ambon city. The population in this research is the people of Ambon city. The research method used is a quantitative method. The sample taken was 100 respondents using a questionnaire distribution technique with a Likert scale. Hypothesis testing uses multiple linear analysis methods with SPSS version 26 tools. The results of this research show that 1) Partially (T test), the product, promotion, place and non-usury variables have a significant influence on the dependent variable "y" because pvalue < 0.05 , while the physical evidence variable does not have a significant influence because the p-value is > 0.05. Simultaneously (F Test) The results of the analysis of perception variables regarding product, promotion, place, physical evidence and usury together influence people's interest in using sharia fintech. This influence is 67.5%. The remaining amount (32.5%) is influenced by other variables outside this research model. Findings underline the importance of enhancing product quality, innovative promotional strategies, and adherence to sharia principles in building consumer trust and interest in sharia fintech. Furthermore, this study reveals the potential of sharia fintech to serve as a more ethical financial alternative, fostering financial inclusion and aligning with the moral values of its users.